1993
DOI: 10.7589/0090-3558-29.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Infectious Disease Agents in Free-Ranging Florida Panthers (Felis Concolor Coryi)

Abstract: Serum samples obtained from 38 free-ranging Florida panthers (Felis concolor coryi) in southern Florida, March 1978 through February 1991, were tested for antibodies against eight bacterial, parasitic, and viral disease agents. Sera were positive for antibodies against feline panleukopenia virus (FPV) (78%), feline calicivirus (56%), feline immunodeficiency virus/puma lentivirus (37%), feline enteric coronavirus/feline infectious peritonitis virus (19%), and Toxoplasma gondii (9%). All samples were seronegativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 17 publications
3
67
5
Order By: Relevance
“…Thus the high antibody prevalence in this study suggests that, at least in some areas, there is considerable immunity, indicating that many mountain lions have been exposed but are now protected against this pathogen. High exposure to FPV is commonly reported in wild felids in North America, including California mountain lions (Paul-Murphy et al, 1994) and Florida panthers (Puma concolor coryi; Roelke et al, 1993). Although we did not detect statistically significant spatial clusters of FPV exposure, there appears to be high antibody prevalence north of the San Francisco Bay area, in Sonoma, Mendocino, and Napa counties, suggesting high levels of population immunity in this region.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Thus the high antibody prevalence in this study suggests that, at least in some areas, there is considerable immunity, indicating that many mountain lions have been exposed but are now protected against this pathogen. High exposure to FPV is commonly reported in wild felids in North America, including California mountain lions (Paul-Murphy et al, 1994) and Florida panthers (Puma concolor coryi; Roelke et al, 1993). Although we did not detect statistically significant spatial clusters of FPV exposure, there appears to be high antibody prevalence north of the San Francisco Bay area, in Sonoma, Mendocino, and Napa counties, suggesting high levels of population immunity in this region.…”
Section: Discussioncontrasting
confidence: 45%
“…Often, kittens are infected periparturiently, as the stress of parturition induces recrudescence and efficient viral shedding of the dam. Prior studies in large North American felids found no exposure to FHV (Roelke et al, 1993;Riley et al, 2004); however an earlier study in California showed 19% antibody prevalence in mountain lions (Paul-Murphy et al 1994). For both FCV and FHV, further investigation to isolate and characterize these pathogens from mountain lions and evaluate the clinical impact of infections in these species is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serologic surveys of free-living mountain lions (Felis concolor) in California and Florida panthers (Felis concolor) indicate an absence of exposure to FeLV (Roelke et al, 1993;Paul-Murphy et al, 1994). In addition, a study by Osofsky et al (1996) indicates that FeLV also is not enzootic in free-living African felids from Botswana.…”
mentioning
confidence: 97%
“…Published reports of similar investigations on wild feline populations are rare (Watson et al, 1981;Heidt et al, 1988;Roelke et al, 1993). Causes of mortality in free-ranging Eurasian lynx also rarely have been documented until now (Stahl and Vandel, 1999).…”
Section: Introductionmentioning
confidence: 99%